Diversifikasi Olahan Kelapa Menjadi Produk Bernilai Ekonomi Tinggi ada Ud Al-Amin, Desa Pemenang Timur, Kecamatan Pemenang, Lombok Utara - Saloko, Satrijo; Rahmatullah, Miftahul Fath; Fikrina, Garin; Ulfa, Maria; Sarkono, Sarkono; Indriyatno, Indriyatno (Universitas Mataram, 2025)
East Pemenang Village, located in Pemenang District, North Lombok Regency, possesses substantial potential in coconut processing; however, most of the harvest is still sold in raw form, resulting in low added value. The Al-Amin Joint Business Group (KUB), which has initiated coconut-based processing such as briquettes and cocopeat, continues to face challenges related to limited technology, insufficient product diversification, and restricted market access. This community engagement program aims to enhance the efficiency of an integrated coconut processing system, develop value-added products such as tropinata beverages, nata de coco, coconut-based soap, and coconut-shell charcoal briquettes, as well as strengthen market linkages. A Supply Chain approach was adopted to integrate upstream and downstream processing activities. The program involved Focus Group Discussions (FGDs), technical training on modern processing technologies, the implementation of new technologies, and continuous mentoring to ensure optimal operational performance. Expected outcomes include product diversification—such as tropinata and coconut-based soap—and increased production capacity, including briquette output reaching 100 kg/day and nata de coco up to 50 liters/day. Furthermore, the program aims to empower the community of East Pemenang Village, improve economic well-being, and establish a sustainable local enterprise ecosystem.